Determination of porosity from shrinkage curves during sintering of granular materials. Issue 5 (4th April 2018) - Mankai, Souhir; Madiouli, Jamel; Sghaier, Jalila; Lecomte, Didier
ABSTRACT: This paper investigates the implementation of an analytical model to determine the porosity of a granular material during reactive and nonreactive sintering. A graphical interpretation of this model is proposed to calculate the porosity by comparing the experimental shrinkage curve with the ideal one. For the nonreactive sintering, some examples have been taken from the literature to illustrate the application of this method for two granular materials (alumina and zircon). In the case of reactive sintering, we have used our experiments to study the sintering behavior of magnesium hydroxide. The shrinkage curve was determined by dilatometer and the porosity was measured by helium pycnometer. The comparison revealed that the porosity calculated from the model is fully consistent with the porosity measurements in the both cases.